أثر تطبيق نظام ذکاء الأعمال على فاعلية اتخاذ القرارات فى المؤسسة العامة للتأمينات الاجتماعية : دراسة حالة - روان محمد عبد الرحيم; Ghada Abdel Wahab (المجلة الدولية لعلوم المكتبات والمعلومات)
The main goal of this study is to know the impact of business intelligencesystem application on the effectiveness of making a decision in the generalorganization for social insurance in Jeddah. This study shows the realimplementation of system of business intelligence and its effect on decisionmaking of the institution and recognize the positive and negative aspects of thisapplication. The study focused on case study methodology where thequestionnaire is a tool for collecting information that has been distributed to thestudy sample by (81) questionnaire, however, (52%) only are received from thetotal distributed. The main results of the study are: The percentage of employeeswho did not receive training and qualification in the field of business intelligenceat the institution reached (92.8%) of the total number of employees responding tothe study. All departments of the institution adopt the business intelligencesystem except the women section and the warehouse department due to theweak infrastructure required by the availability of the system. Moreover, the lackof sufficient technical knowledge and skills among the employees. (35.9%) of theemployees responding to this study indicated that the business intelligencesystem used in the institution is not advanced enough. One of the mostsignificant advantages of implementing business intelligence system is savingtime and effort. One of the main obstacles facing the application of businessintelligence system in the organization is the lack of awareness of the importanceof the business intelligence system to the activities and procedures of the institution, Furthermore, users have not receiving enough training on the systemof business intelligence, and the system of business intelligence is limit to somedepartments. The researcher recommendations are:First of all, providing infrastructure that helps to provide businessintelligence in all departments in the institution. Second, users should havetraining to increase their awareness towards its importance. Third, providing anadvanced system that meets user's needs. Fourth, user's opinions are importantto improve and develop the system. Fifth, encourage users to use the system toworks with high sufficient. Finally, the business intelligence system should beimplemented in the institutions where it has an effective role in decision-making.